Prospecting for Microelement Function and Biosafety Assessment of Transgenic Cereal Plants - Yu, Xiaofen; Luo, Qingchen; Huang, Kaixun; Yang, Guangxiao; He, Guangyuan (Frontiers in Plant Science, 2018)
Microelement contents and metabolism are vitally important for cereal plant growth and development as well as the end-use properties. While minerals phytotoxicity harms plants, microelement deficiency also affects human health. Genetic engineering provides a promising way to solve these problems. As plants vary in abilities to uptake, transport, and accumulate minerals, and the key enzymes acting on that process is primarily presented in this review. Subsequently, microelement function and biosafety assessment of transgenic cereal plants have become a key issue to be addressed. Progress in genetic engineering of cereal plants has been made with the introduction of quality, high-yield and resistant genes since the first transgenic rice, corn and wheat were born in 1988, 1990 and 1992, respectively. As the biosafety issue of transgenic cereal plants has now risen to be a top concern, many studies on transgenic biosafety have been carried out. Transgenic cereal biosafety issues mainly include two subjects, environmental friendliness and end-use safety. Different levels of gene confirmation, genomics, proteomics, metabolomics and nutritiomics, absorption, metabolism and function have been investigated. Lots of work on end-use safety has been carried out, but only limited research regarding environmental friendliness was performed. Also, the different levels of microelement contents have been measured in transgenic plants. Based on the motivation of the requested biosafety, systematic designs and analysis of transgenic cereal are also presented in this review paper.